"A Cool Little Buzz": Alcohol Intoxication in the Dance Club Scene. (3rd July 2014) - Hunt, Geoffrey; Moloney, Molly; Fazio, Adam
<x xml:space="preserve">Abstract</x> In recent years, there has been increasing concern about youthful "binge" drinking and intoxication. Yet the meaning of intoxication remains under-theorized. This paper examines intoxication in a young adult nightlife scene, using data from a 2005–2008 National Institute on Drug Abuse-funded project on Asian American youth and nightlife. Analyzing in-depth qualitative interview data with 250 Asian American young adults in the San Francisco area, we examine their narratives about alcohol intoxication with respect to sociability, stress, and fun, and their navigation of the fine line between being "buzzed" and being "wasted." Finally, limitations of the study and directions for future research are noted.